RECENT TREND ON KNOWN PYRAZOLONE ENDOWED DERIVATIVES: ANOVERVIEW - NEELIMA, G.; ASHA, T.; RUKMINI, S.; BRUNDHA, G. K.; RAJASEKHAR, SREERAMA (International Journal of Current Pharmaceutical Research, 2022)
Pyrazolone is a lactam ring with five-membered and 2-Nitrogen and 1-ketonic groups in its structure. Antimalarial, antifungal, antimycobacterial, antibacterial, anti-inflammatory, anticancer, gastric secretion stimulatory, antidepressant and antifilarial properties are also found in pyrazolones. They are also used in the extraction and separation of various metal ions, as well as precursors for dyes, pigments, insecticides and chelating agents. The excellent therapeutic qualities of pyrazolone-related medicines have prompted medicinal chemistry to develop a slew of new chemotherapeutic treatments. The synthesis of pyrazolone and numerous structural reactions may be done in a variety of ways, which opens up a lot of possibilities in the field of medicinal chemistry. This article mainly reports the chemistry, novel synthesis and biological activity of Pyrazolones and their derivatives.